A Case of de novo; Annular-plaque Type Psoriasis Following Oxford- AstraZeneca COVID-19 Vaccination - Chhabra, Namrata; George, Anju (Current Drug Safety, 2023)
Background: There have been increasing reported cases of new-onset or aggravation of pre-existing dermatoses after the implementation of COVID-19 vaccination. Case Presentation: An elderly male was presented with multiple annular scaly plaques all over the body two weeks following administration of the first dose of Oxford-AstraZeneca COVID-19 vaccine. The lesions further aggravated after taking the second dose of the vaccine. The clinical and histopathology features were suggestive of annular plaque psoriasis. Conclusion: We report this first case of de novo plaque psoriasis following the Oxford- AstraZeneca COVID-19 vaccine, and it signifies a potential side effect of autoimmune reactivation after COVID vaccination.
Keywords: COVID-19 vaccine